2017
DOI: 10.4172/2165-7890.1000197
|View full text |Cite
|
Sign up to set email alerts
|

Further Evidence for Dlgap2 as Strong Autism Spectrum Disorders/Intellectual Disability Candidate Gene

Abstract: Autism spectrum disorders are classified as neurodevelopmental disorders characterised by diminished social communication and interaction. The core symptoms typically coexist with other medical conditions such as intellectual disability. The involvement of rare copy number variations of varying expressivity and penetrance as risk factors in autism spectrum disorders/intellectual disability phenotypes has been highlighted in large series. The DLGAP2 gene, whose glutamatergic postsynaptic density product may pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Unfortunately, DLGAP2 is not expressed in either the placenta or kidney; therefore, investigation of allelic expression with reproducible parent-of-origin methylation in these tissues was not possible. Biallelic DLGAP2 expression was observed in brain, which is consistent with the inheritance of cytogenetically defined deletions and duplications of 8q23.3 from either parent in patients with ASD and intellectual disabilities [28,29]; Decipher database]. Single cell RNA-seq or RNA-FISH analyses are required to confirm random monoallelic expression in brain since single cell clonal expansion is not currently feasible; however, it must be noted that the results from these techniques may not reflect mitotically stable random allelic expression because gene expression within single cells is associated with allelic bursts, which increases the risk of misinterpretation of monoallelic expression at a single time-point [30].…”
Section: Discussionsupporting
confidence: 75%
“…Unfortunately, DLGAP2 is not expressed in either the placenta or kidney; therefore, investigation of allelic expression with reproducible parent-of-origin methylation in these tissues was not possible. Biallelic DLGAP2 expression was observed in brain, which is consistent with the inheritance of cytogenetically defined deletions and duplications of 8q23.3 from either parent in patients with ASD and intellectual disabilities [28,29]; Decipher database]. Single cell RNA-seq or RNA-FISH analyses are required to confirm random monoallelic expression in brain since single cell clonal expansion is not currently feasible; however, it must be noted that the results from these techniques may not reflect mitotically stable random allelic expression because gene expression within single cells is associated with allelic bursts, which increases the risk of misinterpretation of monoallelic expression at a single time-point [30].…”
Section: Discussionsupporting
confidence: 75%
“…Pinto et al (26) suggested that the DLGAP2 gene, located on chromosome 8p23.3, could be a novel candidate gene for ASD. Further evidence for the DLGAP2 gene as a strong candidate gene has been provided by Poquet et al (27) based on several cases with de novo duplications involving the DLGAP2 gene and presenting with ASD. Our patient also had a de novo duplication that included 8p23.3, DLGAP2 gene, respectively.…”
Section: Discussionmentioning
confidence: 90%
“…Thus, 8p12 region was associated with MR (6), 8p23.1 region was associated with MR, ASD (16,19), facial dysmorphism, especially prominent forehead (15,18,20), and CHD (18). 8p21.3→ p23.1 region was associated with MR (5,13,14,17), ADHD (5,17), ASD (27) and CHD (5,13,21). This study shows only one case that has a large duplication involving the entire 8p21.3→ p23.1 region, associated with mild facial dysmorphism with a prominent forehead, MR, ADHD, ASD, and CHD.…”
Section: Discussionmentioning
confidence: 99%
“…The potential role of DLGAP2 in ASD is unclear, however, as one study failed to identify statistically significant difference in frequency of rare missense and nonsense mutations in ASD cases versus controls, although the sample size was small: all cases were Asian, having been recruited in Taiwan (Chien et al, 2013). However, one other study has identified ASD and other neurodevelopmental phenotypes in nine nonoverlapping families with DLGAP2 duplications (Poquet et al, 2017).…”
Section: Discussionmentioning
confidence: 99%